(untitled) (Biological Sciences - PJSIR, 2022)
The present study was conducted to evaluate the feeding behaviour of termite Odontotermes obesus (Ramber) under field conditions under abiotic and biotic factors. Eight wood species include Mangifera indica (mangoes), Albizia lebbeck (albizia), Populus euramericana (popular), Melia azedarach (bead tree), Vachellia nilotica (kiker,thorny acacia), Eucalyptus camaldulensis (eucalyptus), Dalbergia sissoo (shesham) and Eugenia jambolana (Jamun) was offered to termites to feed under field trials. Results found that P. euramericana and M. indica were the most palatable woods to termite. In choice bioassay camaldulensis was more consumed.